Assédio moral no serviço público: a dualidade entre a visibilidade e o enfrentamento ao assédio moral no âmbito da Universidade Federal do Maranhão entre 2021 e 2022 - RODRIGUES, Glaydson Campelo de Almeida (2025)
Between the 1980s and 1990s, Brazil underwent significant transformations marked by the end of the military dictatorship, redemocratization, economic liberalization, and neoliberal policies that prioritized administrative efficiency and market dynamics. Within this context, public sector reforms, including privatizations and outsourcing, altered labor relations, increasing psychosocial challenges and workplace violence, such as moral harassment. In universities, institutions intrinsically linked to society, these transformations highlighted the importance of management focused on valuing human capital, which is indispensable for the generation and dissemination of knowledge. University management faces the challenge of creating favorable conditions for faculty and administrative staff to perform their roles in a collaborative environment aligned with institutional objectives. Moral harassment, defined by Hirigoyen (2002) as abusive behaviors that undermine dignity and well-being, reflects a paradox in the university context: spaces dedicated to ethics and knowledge that can also foster hostility and mental suffering. This study presents an analysis of the specific literature on the topic, addressing the concept and evolution of moral harassment, while tracing the timeline of neoliberalism globally and in Brazil. The primary focus is on labor relations and the conditions that enable the harmful practice of moral harassment. The research is based at the Federal University of Maranhão (UFMA) and reveals, through an analysis of data on employee absenteeism due to illness and institutional documents, that the levels of mental illness are alarming and that the targeted actions and campaigns aimed at raising awareness and preventing moral harassment do not address the structural aspect of the problem but merely individualize it. The absence of a well-defined and integrated institutional policy, combined with a lack of effective support structures, creates an environment that is unfavorable for promoting the quality of life of university employees.